Pengembangan Sistem Informasi Pengaduan Pelayanan Puskesmas Waimangura untuk Meningkatkan Efisiensi dan Akurasi Data Pasien dengan Metode Prototype - Yumiana Mema; Gergorius Kopong Pati; Emirensiana Dappa Ege (Repeater : Publikasi Teknik Informatika dan Jaringan, 2026)
Health services at the Puskesmas (Community Health Center) are an important sector directly related to the community. However, there are still various challenges in patient data management and handling complaints that can hinder service efficiency. One of the efforts to improve service quality is by developing a complaint information system that can efficiently manage and record patient complaints. This study aims to develop a complaint information system for services at the Puskesmas Waimangura using the Prototype method. This method was chosen because of its ability to produce system prototypes that can be immediately tested and developed according to user needs. The system is designed to allow patients to submit complaints related to the services received, as well as enabling Puskesmas staff to follow up on and record each complaint systematically. With the implementation of this system, it is expected to increase efficiency in managing complaint data, speed up problem resolution processes, and improve accuracy in recording patient and complaint data. The results of prototype testing show that this system simplifies the complaint process and provides convenience for staff in following up on patient complaints. The implementation of this information system is expected to improve the quality of services at Puskesmas Waimangura and accelerate responses to issues faced by patients.